Poly (I:C) downregulates platelet production and function through type I interferon - Rivadeneyra, Leonardo; Pozner, Roberto Gabriel; Meiss, Roberto; Fondevila, Carlos; Gómez, Ricardo Martin; Schattner, Mirta (Thrombosis and Haemostasis, 2015)
Thrombocytopenia is a frequent complication of viral infections; the underlying mechanisms appear to depend on the identity of the virus involved. Previous research, including reports from our group, indicates that as well as having antiviral activity type I interferons (IFN I) selectively downregulate platelet production. In this study we extended understanding of the role of endogenous IFN I in megakaryo/ thrombopoiesis by evaluating platelet and megakaryocyte physiology in mice treated with polyinosinic:polycytidylic acid [poly (I:C)], a synthetic analogue of double-stranded RNA, Toll-like receptor-3 ligand and strong IFNp inducer. Mice-treated with poly (I:C) showed thrombocytopaenia, an increase in mean platelet volume and abnormal haemostatic and inflammatory platelet-mediated functionality, indicated by decreased fibrinogen binding and platelet adhesion, prolonged tail bleeding times and impaired P-Selectin externalisation, RANTES release and thrombin-induced platelet-neutrophil aggregate formation. These changes were associated with an increase in size and an abnormal distribution of bone marrow megakaryocytes within the vascular niche and were directly correlated with the plasmatic and bone marrow IFNp levels. All these effects were absent in genetically modified mice lacking the IFN I receptor. Our results suggest that IFN I is the central mediator of poly (I:C)-induced thrombocytopenia and platelet dysfunction and indicate that these abnormalities are due to changes in the last stages of megakaryocyte development. These data provide new evidence for the role of IFN I in megakaryocyte distribution in the bone marrow niches and its influence on thrombopoiesis and haemostasis.
Keywords: Platelets; poly (I:C); thrombocytopaenia; virus; interferon